Visual pathway function and structure in Wolfram syndrome: patient age, variation and progression. Issue 1 (13th January 2018) - Hoekel, James; Narayanan, Anagha; Rutlin, Jerrel; Lugar, Heather; Al-Lozi, Amal; Hershey, Tamara; Tychsen, Lawrence
Abstract : Background/aims: To report alterations in visual acuity and visual pathway structure over an interval of 1–3 years in a cohort of children, adolescents and young adults who have Wolfram syndrome (WFS) and to describe the range of disease severity evident in patients with WFS whose ages differed by as much as 20 years at first examination. Methods: Annual, prospective ophthalmological examinations were performed in conjunction with retinal nerve fibre layer (RNFL) analysis. Diffusion tensor MRI-derived fractional anisotropy was used to assess the microstructural integrity of the optic radiations (OR FA). Results: Mean age of the 23 patients with WFS in the study was 13.8 years (range 5–25 years). Mean log minimum angle resolution visual acuity was 0.66 (20/91). RNFL thickness was subnormal in even the youngest patients with WFS. Average RNFL thickness in patients with WFS was 57±8 µ or ~40% thinner than that measured in normal (94±10 µ) children and adolescents (P<0.01). Lower OR FA correlated with worse visual acuity (P=0.006). Subsequent examinations showed declines (P<0.05) in visual acuity, RNFL thickness and OR FA at follow-up intervals of 12–36 months. However, a wide range of disease severity was evident across ages: some of the youngest patients at their first examination had deficits more severe than the oldest patients. Conclusion: The genetic mutation of WFS causes damage to both pregeniculate and postgeniculate regions of the visual pathway. The damage is progressive. The decline in visual pathway structure is accompanied by declines of visual function. Disease severity differs widely in individual patients and cannot be predicted from their age.